ANALYSIS OF DIGITAL MARKETING STRATEGIES ON INTEREST AND ENROLLMENT DECISIONS OF PROSPECTIVE NEW STUDENTS IN PRIVATE HIGHER EDUCATION INSTITUTIONS IN INDONESIA (A CASE STUDY OF JAKARTA GLOBAL UNIVERSITY) - Hadi Wijaya; RM Chairil Andri; Dwi Rachmawati (Faculty of Economics and Business, Universitas Klabat, 2023)
The research investigates the impact of Google Adwords Advertising and Social Media Marketing on the interest to register (enrollment) and enrollment decisions of potential new students at Global University Jakarta (JGU). In Indonesia, Private Higher Education Institutions (PTS) make up 66.27% of the total higher education institutions, facing intense competition for prospective students, particularly from Generation Z. The COVID-19 pandemic has expedited the transition to digital activities, necessitating continuous adaptation by universities. Generation Z, characterized by 100% internet usage and high smartphone ownership, demands innovative digital marketing strategies. The study employs a quantitative approach, collecting data through questionnaires from 172 first- and second-semester students at JGU. Path analysis is utilized to examine the relationships between Google Adwords Advertising, Social Media Marketing, interest to register, and enrollment decisions. The results indicate that both Google Adwords Advertising and Social Media Marketing significantly and positively influence the interest to register. Furthermore, interest to register significantly affects enrollment decisions. These findings emphasize the significance of effective digital marketing strategies in influencing prospective students' interest and enrollment decisions. Given that digital marketing dynamics evolve alongside changing technologies and platform algorithms, regular analysis and adaptation are recommended. This study aim to provide valuable insights for educational institutions, encouraging the utilization of Google Adwords Advertising and Social Media Marketing to enhance enrollment among prospective students. Keywords: Digital marketing, Google adwords advertising, social media marketing, interest to register, enrollment decisions.